Core Shell Regulations in Co-Precipitation to Regulate Structure and Performance of Single-Crystal NCM622 - Siburian, Donny Marihot; Cheng Yi; Liu Hai; Zhen Jiang He; Hua Wenchao; Xu Kaihua (Science and Technology Indonesia, 2025)
The development of single-crystal NCM622 cathodes remains a key focus in lithium-ion battery research due to their stable structure and cycling performance. This study explores the impact of controlled gas environments on particle nucleation and growth, particularly under different nitrogen-to-air (N₂:air) ratios. The optimized condition, Hydroxide precursor (HP)-2.5 and Single crystal cathode (SC)-2.5 (N₂:air = 2.4:0.2 during nucleation up to 2.5 μm, followed by N₂:air = 2.4:0 for growth up to 5 μm), facilitates the formation of well-structured particles with a core-shell morphology. This structure enhances sintering efficiency, leading to the successful formation of single-crystal NCM622. Electrochemical evaluations reveal that SC-2.5 exhibits excellent cycling stability, with an initial discharge capacity of 168.48 mAh/g and a retention of 134.81 mAh/g after 100 cycles. The capacity retention of 86.32% and Coulombic efficiency of 99.32% indicate minimal degradation and strong electrochemical stability. These findings highlight the importance of controlled synthesis conditions in optimizing lithium-ion battery cathodes for high-performance energy storage applications.